2016
DOI: 10.1111/cge.12856
|View full text |Cite
|
Sign up to set email alerts
|

Genetic causes of moderate to severe hearing loss point to modifiers

Abstract: The genetic underpinnings of recessively inherited moderate to severe sensorineural hearing loss are not well understood, despite its higher prevalence in comparison to profound deafness. We recruited 92 consanguineous families segregating stable or progressive, recessively inherited moderate or severe hearing loss. We utilized homozygosity mapping, Sanger sequencing, targeted capture of known deafness genes with massively parallel sequencing and whole exome sequencing to identify the molecular basis of hearin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 32 publications
0
29
0
Order By: Relevance
“…Seven new likely pathogenic variants (c.945G>A [p.(Trp315*)], c.1143C>G [p.(Tyr381*)], c.1209G>A [p.(Trp403*)], c.1224+2T>C, c.1259G>A [p.(Cys420Tyr)], c.1728C>G [p.(Asn576Lys)], and c.1753_1754insA [p.(Asn407Lysfs*2)]) were identified in our cohort (Table and ). In contrast, the c.482+1986_88delTGA allele of HGF accounts for HL segregating in 26 families (Table ), which was already identified as a founder allele in 50 other Pakistani families in our collaborative studies (Naz et al., ; Rehman et al., ; Schultz et al., ). Similarly, the c.272T>C allele of CIB2 accounts for the HL phenotype segregating in 15 families (Table ).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Seven new likely pathogenic variants (c.945G>A [p.(Trp315*)], c.1143C>G [p.(Tyr381*)], c.1209G>A [p.(Trp403*)], c.1224+2T>C, c.1259G>A [p.(Cys420Tyr)], c.1728C>G [p.(Asn576Lys)], and c.1753_1754insA [p.(Asn407Lysfs*2)]) were identified in our cohort (Table and ). In contrast, the c.482+1986_88delTGA allele of HGF accounts for HL segregating in 26 families (Table ), which was already identified as a founder allele in 50 other Pakistani families in our collaborative studies (Naz et al., ; Rehman et al., ; Schultz et al., ). Similarly, the c.272T>C allele of CIB2 accounts for the HL phenotype segregating in 15 families (Table ).…”
Section: Discussionmentioning
confidence: 72%
“…For instance, two families (HL007 and DEM4372) display locus heterogeneity, within the same or different branches, segregating homozygous variants in two different known NSARHL genes (Figure ), which further highlights the unexpected complexity of the genetic diagnosis of HL in consanguineous families. In the family HL007, most of the affected individuals are homozygous either for a reported c.1056G>A, p.(Trp352*) variant of TPRN , (Rehman et al., ), or another reported c.7814A>G, p.(Asn2605Ser) variant in CDH23 (Naz et al., ) a gene known to be involved in either NSARHL or Usher syndrome type 1D (MIM# 601067) (Bork et al., ). Affected individual VII:3 is homozygous for both of the likely pathogenic variants of TPRN and CDH23 (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…All scale bars 20 µm. In addition to Slc26a4, deafness genes expressed in spindle cells include Ceacam16, Cldn14, and P2rx2 (Wilcox et al, 2001;Ben-Yosef et al, 2003;Zheng et al, 2011;Faletra et al, 2014;Naz et al, 2017;Zhu et al, 2017;Booth et al, 2018). More importantly, these data demonstrate the possibility that some of these deafness genes affect multiple SV cell types, as in the case of Mitf and Supplementary Figure S9.…”
Section: Deafness Gene Mapping Suggests a Role For Sv Cell Types In Hmentioning
confidence: 74%
“…Consistent with previous studies [17], all three probands with STRC homozygous or compound heterozygous deletions have moderate hearing loss (PTAs of 40-50 dB HL). Fourteen of the sixteen other independent mutations identified in this study have been reported to be associated with hearing loss in previous studies, including dominant mutations EYA1 c.1276G > A (p. G426S) [18] and MITF c.877C > T (p. R293*) [19], recessive mutations PCDH15 c.4133C > T (p. T1378I) and c.1453delT (p. S485Rfs*2) [20], USH2A c.10904C > A (p.T3635 N) [21], MYO15A c.8158G > A (p. D2720N) and c.10258_10260delTTC (p.F3420-) [22], CDH23 c.7630 T > G (p. L2544 V) and c.8257G > A (p.A2753T) [20], OTOF c.2122C > T (p.R708*) and c.1194 T > A (p.D398E) [23,24], SLC26A4 c.1174A > T (p. N392Y) and c.1975G > C (p.V659 L) [25], and SMPX c.55A > G (p. N19D) [26]. One novel hemizygous mutation, c.201delT (p.E68Sfs*11) in TIMM8A, was identified in a male proband D211 as a likely pathogenic mutation since similar Based on the new genetic diagnosis, we revisited the clinical aspects of proband D289 and D554.…”
Section: Additional or Alternative Causes In Patients With Monoallelimentioning
confidence: 99%